2023
DOI: 10.3390/ph16091272
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Therapy in Inflammatory Bowel Diseases: A Narrative Review of the Past 90 Years

Marcello Imbrizi,
Fernando Magro,
Claudio Saddy Rodrigues Coy

Abstract: Inflammatory Bowel Diseases had their first peak in incidence in countries in North America, Europe, and Oceania and are currently experiencing a new acceleration in incidence, especially in Latin America and Asia. Despite technological advances, 90 years after the development of the first molecule for the treatment of IBD, we still do not have drugs that promote disease remission in a generalized way. We carried out a narrative review on therapeutic advances in the treatment of IBD, the mechanisms of action, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 125 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Inflammatory bowel diseases (IBDs) such as Crohn's disease (CD) and ulcerative colitis are the result of an over-reactive immune system that targets the gastrointestinal tissue, resulting in inflammation and subsequent abdominal pain, bleeding, weight loss, and malnutrition [53][54][55][56][57]. Several studies have shown that LFA-1 plays a crucial role in the development of the disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs) such as Crohn's disease (CD) and ulcerative colitis are the result of an over-reactive immune system that targets the gastrointestinal tissue, resulting in inflammation and subsequent abdominal pain, bleeding, weight loss, and malnutrition [53][54][55][56][57]. Several studies have shown that LFA-1 plays a crucial role in the development of the disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Gut microbiota and its dysregulation are one of the environmental factors that also play a key role in the immune-mediated disease process of IBD. Thus, various medical therapies target these pathophysiologic pathways [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the diseases mentioned above, IBD is one of the contexts in which barrier function has been most intensively researched. IBD is a collective term for a group of inflammatory diseases of the gut, including ulcerative colitis (UC) and Crohn’s disease (CD), and it is a chronic inflammatory disease of unknown cause [ 9 , 10 ]. It was originally described as a disease that more commonly affects Caucasians, but now, patients are rapidly increasing in Asia, including Japan, although there are limited epidemiological data from developing countries [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review summarizes intestinal barrier function, including the microbiome involvement (Figure 1), and further focuses on a comparison of the barrier functions of tight junction proteins and the membrane permeability between patients with UC or CD and healthy subjects. (CD), and it is a chronic inflammatory disease of unknown cause [9,10]. It was originally described as a disease that more commonly affects Caucasians, but now, patients are rapidly increasing in Asia, including Japan, although there are limited epidemiological data from developing countries [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%